Tinjauan Biblika Terhadap Tujuan Ucapan Kutuk Elisa Dalam 2 Raja-Raja 2:23-25 - Harefa, Yaaro; Ilo, Yolin (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2023)
Abstract: Elisha's act of cursing the children in 2 Kings 2:23-25 raises many perceptions and even makes it difficult for readers to understand texts like this. How could a man of God utter such a curse word? Therefore, the researcher investigated this topic using a qualitative method with an exegetical approach. The researcher found that this text is not problematic if the reader can understand the purpose behind Elisha's words. Prophecy is entirely God's decision and action for the benefit of His people. This is a special task that God has given him to do on this earth. Accepting and honoring God's messengers is a form of acceptance of God through the Word that is delivered. The truth they preach is the truth of God's grace for man to attain salvation in Christ. Humans are given two choices, namely accepting the truth of God's Word or turning away from God, because God has given free will for humans to choose. The punishment given to those who reject God is the eternal punishment to come.Abstrak: Tindakan Elisa dalam mungutuk anak-anak dalam 2 Raja-Raja 2:23-25 menimbulkan banyak persepsi bahkan akhirnya menjadi hal sulit bagi pembaca untuk memahami teks-teks seperti ini. Bagaimana mungkin seorang hamba Tuhan mengutarakan kata kutuk seperti ini? Oleh sebab itu peneliti menyelidiki topik ini menggunakan metode kualitatif dengan pendekatakan eksegesis. Peneliti menemukan bahwa teks ini tidak bermasalah jika pembaca bisa mememahami tujuan dibalik ucapan Elisa ini. Nabi adalah sepenuhnya keputusan dan tindakan Allah untuk kepentingan umat-Nya. Ini adalah satu tugas istimewa yang Tuhan berikan untuk dikerjakan di muka bumi ini. Menerima dan hormati utusan Tuhan sebagai bentuk penerimaan akan Tuhan melalui Firman yang disampaikan. Kebenaran yang mereka beritakan adalah kebenaran kasih karunia Tuhan bagi manusia untuk mencapai keselamatan di dalam Kristus. Manusia diberi dua pilihan yaitu menerima kebenaran Firman Tuhan atau berpaling dari Tuhan, karena Tuhan sudah memberikan kehendak bebas bagi manusia untuk memilih. Hukuman yang diberikan kepada yang menolak Allah adalah hukuman kekal yang akan datang.